THE SHEIKH OF THE NAQSHBANDI TARIQA OF THE 19TH CENTURY, SALAHIDDIN IBN MAWLANA SIRAJIDDIN OSHI (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Sufism has a special place in the history of Islam. Sufism deputies (Awliya, Shaikh, Murshid, Pir, Ishan) had great effects on the spread and acceptance of Islam, especially in the Central Asia. The Kübraviye, Sühraverdiye, Yeseviye and Nakşibendiye tariqats which were laid in the Central Asian region, acted as a catalyst in the Islamization of the region. These tariqats have had a great impact not only on the religious issue but also on the civil cultural area of the region. In particular, the Nakshi-Mujaddidiyye school has continued to exist until recent times, expanding its fields of influence and activity. In this article, brief information will be given about the life, works and activities of Salah Ad-Din Ishan from Osh, one of the last shaikhs of the Nakshi-Mujaddidiyye tariqat.
Keywords: Nakshbandiyya, Tariqat, Sufism, Huvayda, Salah ad-Din Ishan, Thaqib, Osh, Sarmazar.